Distribution of HLA-DQ risk genotypes for celiac disease in Ethiopian children - Gudeta Adugna N; Ramelius Anita; Balcha Taye T; Girma Alemayehu; Ilonen Jorma; Agardh Daniel (WILEY, 2025)
Most patients with celiac disease are positive for either HLA-DQA1*05:01-DQB1*02 (DQ2.5) or DQA1*03:01-DQB1*03:02 (DQ8). Remaining few patients are usually DQA1*02:01-DQB1*02 (DQ2.2) carriers. Screenings of populations with high frequencies of these HLA-DQA1-DQB1 haplotypes report a 1% to 3% celiac disease prevalence. The aim was to determine the prevalence of HLA-DQ risk haplotypes for celiac disease in Ethiopian children. Dried blood spots collected from 1193 children from the Oromia regional state of Ethiopia were genotyped for HLA-DQA1 and DQB1 genotyping using an asymmetric polymerase chain reaction (PCR) and a subsequent hybridization of allele-specific probes. As references, 2000 previously HLA-genotyped children randomly selected from the general population in Sweden were included. DQ2.2 was the most common haplotype and found in 15.3% of Ethiopian children, which was higher compared with 6.7% of Swedish references (P < .0001). Opposed to this finding, DQ2.5 and DQ8 occurred in 9.7% and 6.8% of Ethiopian children, which were less frequent compared with 12.8% and 13.1% of Swedish references, respectively (P < .0001). The DQ2.5-trans genotype encoded by DQA1*05-DQB1*03:01 in combination with DQ2.2 occurred in 3.6% of Ethiopian children, which was higher compared with 1.3% of Swedish references (P < .0001). However, when children with moderate high to very high-risk HLA genotypes were grouped together, there was no difference between Ethiopian children and Swedish references (27.4% vs 29.0%) (P = .3504). The frequency of HLA risk haplotypes for celiac disease is very similar in Ethiopian and Swedish children. This finding of importance will be useful in future screening of children for celiac disease in Ethiopia.